The Updated Change Trend of Sea Wave on Vietnam East Sea - Van My, Tran; Xuan Hien, Nguyen; Quoc Huy, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 3DO - 10.25073/2588-1094/vnuees.4688, 2021)
The annual mean SWH trend of the East Sea in Vietnam is studied and evaluated based on data observed from the oceanographic stations and altimetry data from AVISO’s satellite. Oceanographic observed data analysis results show that the annual mean sea wave height decreases about 12,79 mm/year. Altimetry data (2009 – 2019) indicates that the annual mean sea wave height over the East Sea decreases about 6,2 mm/year. The annual mean sea wave height along the Viet Nam coast has a decreasing trend of about 13 mm/year. The North Central Coastal region of Viet Nam has the strongest downward trend with being about 17 mm/year while the South Central coastal and Southern area shows a decrease at about 3,0 mm/year.